WATER AND THERMAL-RESISTANT PROPERTIES OF STARCH-BASED COMPOSITES REINFORCED WITH PLANT CELLULOSE - Opamawutthikul, Monluedee; Srirachya, Nuttida (PSRU Journal of Science and Technology, 2024)
Starch is a polymer material widely used in biomaterial area. Due to its limitations in strength and stability, this study investigated appropriate type and amount of cellulose for strengthening stability, water-resistant, and thermal-resistant properties of starch-based composites. Selected cellulose fibers in this study were tala palm ones for the short and rami ones for the long. Initially, chemical pretreatment (10% NaOH, 4% H2SO4 and 10% NaOCl) was carried out to remove the lignins and hemicelluloses. Then the proper proportions between starch (matrix) and cellulose (reinforcement) were determined. The mixtures were molded using heat-moisture drying technique at 40˚C. Water-resistant tests were carried out by immersing the samples in water at room temperature for 60 minutes. Meanwhile, thermal-resistant tests were executed at 100˚C for 60 minutes. The samples were finally assessed the stability. It was found that the proper proportion was the suspension of starch 1: water 3 and 1% wt. pretreated cellulose. When molded, all the samples remained shapes as molded, no cracking and no breaking. Apparently, the top surfaces of samples became rough according to the spreading of the fibers. It was obvious that tala palm fibers were generally embedded in the surrounding matrix, hence appeared better adhesion to the matrix phase than that of rami ones. At this unsimilar point, it caused different stable appearances under similar hydrated and heated conditions. Therefore, the composites reinforced with tala palm cellulose provided the better stability. This is useful for applying for water- and thermal-resistant green packaging.